Perindopril arginine: a new ACE inhibitor salt increases therapeutic potential - Yu. A. Karpov (Кардиоваскулярная терапия и профилактика)
Perindopril is one of the most effective ACE inhibitors used for cardiovascular disease treatment. At the moment, perindopril is used as perindopril tert butylamine with limited "shelf life"; the medication should be specially packed for the countries with hot and humid climate. To increase medication stability and "shelf life", a new perindopril salt was introduced for wide clinical use - perindopril arginine. Experimental and clinical studies demonstrated complete bioequivalence of this new salt, comparing to the old one, provided the dose is increased from 4-8 mg (perindopril tert butylamine) to 5-10 mg (perindopril arginine), due to molecular weight difference.